Immediate versus delayed loading of strategic mini dental implants for the stabilization of partial removable dental prostheses: a patient cluster randomized, parallel-group 3-year trial. Issue 1 (December 2017) - Mundt, Torsten; Al Jaghsi, Ahmad; Schwahn, Bernd; Hilgert, Janina; Lucas, Christian; Biffar, Reiner; Schwahn, Christian; Heinemann, Friedhelm
Abstract Background Acceptable short-term survival rates (>90 %) of mini-implants (diameter < 3.0 mm) are only documented for mandibular overdentures. Sound data for mini-implants as strategic abutments for a better retention of partial removable dental prosthesis (PRDP) are not available. Methods/design The purpose of this study is to test the hypothesis that immediately loaded mini-implants show more bone loss and less success than strategic mini-implants with delayed loading. In this four-center (one university hospital, three dental practices in Germany), parallel-group, controlled clinical trial, which is cluster randomized on patient level, a total of 80 partially edentulous patients with unfavourable number and distribution of remaining abutment teeth in at least one jaw will receive supplementary min-implants to stabilize their PRDP. The mini-implant are either immediately loaded after implant placement (test group) or delayed after four months (control group). Follow-up of the patients will be performed for 36 months. The primary outcome is the radiographic bone level changes at implants. The secondary outcome is the implant success as a composite variable. Tertiary outcomes include clinical, subjective (quality of life, satisfaction, chewing ability) and dental or technical complications. Discussion Strategic implants under an existing PRDP are only documented for standard-diameter implants. Mini-implants could be a minimal invasive and low cost solution for this treatment modality. Trial registration The trial is registered at Deutsches Register Klinischer Studien (German register of clinical trials) under DRKS-ID:DRKS00007589 (www.germanctr.de ) on January 13th, 2015.